Mast cell infiltration associated with loss of interstitial cells of Cajal and neuronal degeneration in achalasia - Liu, Zu‐Qiang; Chen, Wei‐Feng; Wang, Yun; Xu, Xiao‐Yue; Zeng, Yi‐Gang; Lee Dillon, Dustin; Cheng, Jing; Xu, Mei‐Dong; Zhong, Yun‐Shi; Zhang, Yi‐Qun; Yao, Li‐Qing; Zhou, Ping‐Hong; et al. (Neurogastroenterology and motility, 2019)
Background Achalasia is a motility disorder of unknown etiology. Previous studies supported the hypothesis that autoimmune‐mediated inflammatory responses produce inhibitory neuronal degeneration. This study was designed to explore the role of mast cells in achalasia. Methods We collected information from 116 patients with achalasia who underwent peroral endoscopic myotomy between December 2016 and May 2017. Lower esophageal sphincter (LES) muscle biopsy was performed in all patients with achalasia, as well as 20 control subjects. The number of mast cells, interstitial cells of Cajal (ICCs), nNOS‐positive cells, and S‐100‐positive cells in the LES were evaluated by immunohistochemistry. Pathological and clinical data were compared between groups. Key Results Compared with controls, the LES of patients with achalasia had significantly fewer ICCs, nNOS‐positive cells, and S‐100‐positive cells and a higher number of mast cells (all P < 0.001). Furthermore, the increased mast cell infiltration was significantly associated with decreased ICCs, nNOS‐positive cells, and S‐100‐positive cells in patients with achalasia (all P < 0.05). Clinically, the number of strongly positive mast cells was highest in patients with type I achalasia and lowest in those with type III achalasia (P < 0.001). In addition, patients with a history of autoimmune disease or viral infection had greater mast cell infiltration in the LES muscle (P = 0.040). Conclusions & Inferences In patients with achalasia, mast cell infiltration in the LES muscle is increased, in association with loss of ICCs and neuronal degeneration. Mast cells may thereby play a crucial role in the development of achalasia. Achalasia is a motility disorder with unknown etiology. It has been proposed that autoimmune‐mediated inflammatory responses play an important role in the etiology of inhibitory neuronal degeneration in achalasia. Patients with achalasia had increased infiltration of mast cells in their lower esophageal sphincter muscle, which was associated with loss of interstitial cells of Cajal, neuronal degeneration, the type of achalasia, and a history of autoimmune disease or viral infection. Mast cells may play a crucial role in the development of achalasia.